Experimental and analytical investigation of ferrocement water pipe - KUMAR, N.KRANTHI; thukkaiah, A (The journal of contemporary issues in business and government, 2020)
Ferrocement is kind of reinforcing concrete. It generally comprised of hydraulic cement mortar reinforced with closely spaced layers of continuous and very tiny size wire mesh. The mesh may be composed of metallic or other appropriate materials (Blake, 2001). (Blake, 2001). It is cheap cost, robust, weather-resistance, lightweight and notably its adaptability compared to the reinforced concrete (Ali, 1995). (Ali, 1995). Robles-Austriaco et al. (1981) revealed that ferrocement is an effective material for home building. Also Al-Kubaisy and Jumaat (2000) explored the feasibility of utilizing ferrocement cover in the stress zone of reinforced concrete slab. This material is also utilized in mending the reinforcing element such as beams, slabs or walls (Fahmy et al. 1997; Elavenil and Chandrasekar, 2007; Jumaat, 2006). (Fahmy et al. 1997; Elavenil and Chandrasekar, 2007; Jumaat, 2006). Mourad and Shang (2012) employed ferrocement jacket in restoring reinforced concrete column.